KARAKTERISTIK DAN KERAPATAN SARANG ORANGUTAN (Pongo pygmaeus wurmbii) DI DUA TIPE HABITAT YANG BERBEDA DI STASIUN PENELITIAN CABANG PANTI TAMAN NASIONAL GUNUNG PALUNG KABUPATEN KAYONG UTARA - Hakim, Arif Firman; Prayogo, Hari; Siahaan, Sarma (Universitas Tanjungpura, 2019)
Cabang Panti Research Station has diverse habitat, therefore the researchers are interested to conducting a research on the characteristic and densities of Orangutan nests (Pongo pygmaeus wurmbii) in two on different habitat namely in alluvial bench forests and peat swamp forests. The purpose of this study want to see a comparison of the characteristic and density as an Orangutan nest (Pongo pygmaeus wurmbii) in two different habitat types. The method used in this research was Line transect survey. The nests were searched by walking through the midline while observing and recording the discovered nests in the line transect. Based on the result of the Independent Sample Test, it showed that there was no difference of tree trunk diameter, but there was a difference of height of the nest tree and the nest itself. The nest position was almost similar which was position 3 (tip top) in the amount of 83% in alluvial bench habitat while it was position 1 (among the main branching) in the amount of 42% and 3 (the canopy of the tree in form of fork) in the amount of 42%. The class of the nest which mostly found in both habitat was nest class D in the amount of 50% in the alluvial bench habitat and 83% in the peat swamp forest. The type of tree which was mostly used by the Orangutan to create their nest in both habitat was Shorea spp. The densities of the nest of Orangutan was 30 nest/km² in the alluvial bench habitat and 60 nest/km² in the peat swamp habitat. Keyword: Cabang Panti, Nest Characteristics, Nest Densities, Orangutan